Characteristics of people attending psychiatric clinics in inner Sydney homeless hostels. Issue 4 (5th March 2018) - Nielssen, Olav B; Stone, William; Jones, Naidene M; Challis, Sarah; Nielssen, Amelia; Elliott, Gordon; Burns, Nicholas; Rogoz, Astrid; Cooper, Lucy E; Large, Matthew M
Abstract: Objective: To describe the characteristics of people attending mental health clinics at shelters for the homeless in inner city Sydney. Design: Retrospective review of medical records of homeless hostel clinic attenders. Setting: Mental health clinics located in three inner city homeless hostels. Participants: Consecutive series of clinic attenders, 21 July 2008 – 31 December 2016. Main outcome measures: Demographic characteristics; social, medical and mental health histories of homeless people. Results: 2388 individual patients were seen at the clinics during the 8.5‐year study period. Their mean age was 42 years (standard deviation, 13 years), 93% were men, and 56% were receiving disability support pensions. 59% of attenders had been homeless for more than a year, and 34% of all attenders reported sleeping in the open. The most common diagnoses were substance use disorder (66%), psychotic illness (51%), acquired brain injury (14%), and intellectual disability (5%). Most patients had more than one diagnosis. Early life and recent trauma was reported by 42% of patients. Pathways to homelessness included release from prison (28% of the homeless), discharge from a psychiatric hospital (21%), loss of public housing tenancy (21%), and inability to pay rent because of problem gambling. Conclusions: The high rates of substance use and mental disorder among homeless people in inner Sydney confirms the need for increased access to treatment for these conditions in this setting. Homelessness among those with mental illness might be reduced by developing alternative housing models, and supporting people with multiple problems to retain tenancy.